Understanding the association between endothelial dysfunction and left ventricle diastolic dysfunction in development of coronary artery disease and heart failure - Sušić, Livija; Maričić, Lana; Vincelj, Josip; Vadoci, Milena; Sušić, Tihomir (Acta Biomedica Atenei Parmensis, 2021)
Cardiovascular diseases (CVDs) have been the most common cause of death worldwide for decades. Until recently the most affected patients were middle-aged and elderly, predominantly men, with more frequent ST elevation myocardial infarction (STEMI) caused by obstructive coronary artery disease (CAD). However, in the last two decades we have noticed an increased incidence of ischemia with non-obstructive coronary arteries (INOCA), which includes myocardial infarction with non-obstructive coronary arteries (MINOCA) and non-myocardial infarction syndromes, such as microvascular and vasospastic angina, conditions that have been particularly pronounced in women and young adults - the population we considered low-risky till than. Therefore, it has become apparent that for this group of patients conventional methods of assessing the risk of future cardiovascular (CV) events are no longer specific and sensitive enough. Heart failure with preserved ejection fraction (HFpEF) is another disease, the incidence of which has been rising rapidly during last two decades, and predominantly affects elderly population. Although the etiology and pathophysiology of INOCA and HFpEF are complex and not fully understood, there is no doubt that the underlying cause of both conditions is endothelial dysfunction (ED) which further promotes the development of left ventricular diastolic dysfunction (LVDD). Plasma biomarkers of ED, as well as natriuretic peptides (NPs), have been intensively investigated recently, and some of them have great potential for early detection and better assessment of CV risk in the future.